Simulações numéricas do fluxo de água doce no início do Holoceno: implicações para o sistema climático - Santos, Reginaldo Tudeia dos (Universidade Federal do Rio Grande do Norte, 2020)
The Early Holocene (EH) is marked by the transition of glacial/interglacial conditions with a tendency of heating in some regions of the planet registered in proxy and in reconstructions of temperature. Climatic models such as SPEEDY/HYCOM can simulate the influence of the reduction of the polar ice layers as a result of the increase of the temperature of the EH, in addition to other forcing that influenced the climatic system of the time. In this paper, we will cover the impact of the extra pulse of freshwater to ocean and aggregate systems, through simulations with SPEEDY/HYCOM and SPEEDY/HYCOM/MODF coupled atmospheric-oceanic climate models, from a control climate we call of Pre-industrial and a climate referring to the period of Holocene beginning, (~ 11kyr), where there is insertion of freshwater in the Labrador Sea. We also implemented a change in the model code, where we added a new parameterization related to the freshwater flux. The simulations were 1,500 years for the EH and 200 years for the PI, with EH with extra freshwater. We used statistical methods to analyze climate responses in relation to oceanic and atmospheric circulation. The results indicated, for example, a cooling of the SST, in the EH, in the region of the North Atlantic, in the months of JFM, whereas for JJA a warming of up to 0.7 ° C occurred, whereas in the other oceans the SST was superior to those of the IP, both in winter and in austral summer except in a small Pacific region where the anomaly was up to -0.8 ° C in JFM. Regarding the surface temperature conditions (TS), the simulations indicated a more intense heating profile in the EH and may be related to, for example, the variation of sunlight on an orbital scale. As for EH precipitation and evaporation, the results pointed to a positive precipitation anomaly in the Bering Sea, China, southern parts of Greenland and Labrador. Regarding evaporation, the standard deviation for the difference between evaporation and precipitation showed low variability in the equatorial range and ...